The Effect of Song Learning Media and English Communicative Mastery on English Speaking Ability - Amirrudin Amirrudin (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The purpose and specific target of this research is to find out how much influence learning media learning through songs and mastery of communicative English (English Communicative) has on English speaking ability. The research method used is descriptive quantitative with survey technique. In this study, a representative sample of 90 people was taken. The data collection technique was carried out by distributing questionnaires to the object to be studied using a Likert scale. The data source is primary data, analyzed with a descriptive statistical approach to determine the frequency of answers and percentages. The results prove that the effect of song learning media and mastery of English Communicative on English speaking ability is positive and significant. There is a significant influence of song learning media and mastery of English Communicative on students' English speaking ability in South Jakarta. The regression coefficient is significant as shown by Sig value 0.000 <0.05 and Fcount 120.520. From the results obtained, it can be concluded that the long-term goal of learning by using learning media through English songs can be used as an important alternative media in mastering everyday English. The purpose and specific target of this research is to find out how much influence learning media learning through songs and mastery of communicative English (English Communicative) has on English speaking ability. The research method used is descriptive quantitative with survey technique. In this study, a representative sample of 90 people was taken. The data collection technique was carried out by distributing questionnaires to the object to be studied using a Likert scale. The data source is primary data, analyzed with a descriptive statistical approach to determine the frequency of answers and percentages. The results prove that the effect of song learning media and mastery of English Communicative on English speaking ability is positive and significant. There is a significant influence of song learning media and mastery of English Communicative on students' English speaking ability in South Jakarta. The regression coefficient is significant as shown by Sig value 0.000 <0.05 and Fcount 120.520. From the results obtained, it can be concluded that the long-term goal of learning by using learning media through English songs can be used as an important alternative media in mastering everyday English.